Improving The Quality Of Manufacturing Products With The Application Of Lean Six-Sigma - H Harisupriyanto; Yudha Prasetiawan; M Ferdian Rahma Supri (Institut Teknologi Dirgantara Adisutjipto, 2019)
Product quality is an important factor that underlies the consumer's decision to choose the desired product and service. Quality can initially be determined by the company, but in subsequent developments, quality planning must pay attention to the wants and needs of consumers. In providing excellent service to customers, the company needs to apply the concept of lean thinking, intending to reduce waste. A methodology is needed that can reduce product variations and production process errors with the Six Sigma methodology. The second application is often called Lean Six Sigma. This paper aims to improve the quality of fluid carrier tank products. The number of defective products, mainly on welding, cutting and bending process, so rework is needed that causes companies to suffer losses. The company expects to reduce product defects by less than 5%. The welding, cutting and bending process are the highest contributor to defective products, so that process improvement is limited to these processes. The process of welding, cutting and bending process is considered a major problem, so the main concern for quality improvement is for the main problem. Sigma, the initial welding, cutting and bending process in a sequence is quite good. The target to be achieved is to increase the sigma value of both processes. The alternative is chosen, namely creating and supervising SOPs, and training to improve the skills, knowledge, and abilities of each employee. These alternatives can increase the sigma value from the initial conditions from 2.93 to 3.20. The increase in sigma value indicates a decrease in the level of defects per million opportunities (DPMO).